Knowledge, attitudes and practices on influenza vaccination during pregnancy in Quito, Ecuador - Carlos E. Erazo; Carlos V. Erazo; Mario J. Grijalva; Ana L. Moncayo (BMC, 2021)
Abstract Background Vaccination is the most effective way to prevent infection and severe outcomes caused by influenza viruses in pregnant women and their children. In Ecuador, the coverage of seasonal influenza vaccination in pregnant women is low. The aim of this study was to assess the knowledge, attitudes, and practices (KAP) of pregnant women toward influenza vaccination in Quito-Ecuador. Methods A cross-sectional study enrolled 842 women who delivered at three main public gynecological-obstetric units of the Metropolitan District of Quito. A questionnaire regarding demographics, antenatal care, risk conditions and knowledge, attitudes and practices related to influenza vaccination was administered. We examined factors associated with vaccination using log-binomial regression models. Results A low vaccination rate (36.6%) against influenza was observed among pregnant women. The factors associated with vaccination included the recommendations from health providers (adjusted PR: 15.84; CI 95% 9.62-26.10), belief in the safety of the influenza vaccine (adjusted PR: 1.53; CI 95% 1.03-2.37) and antenatal care (adjusted PR: 1.21; CI 95% 1.01-1.47). The most common reasons for not vaccinating included the lack of recommendation from health care providers (73.9%) and lack of access to vaccine (9.0%). Conclusions Health educational programs aimed at pregnant women and antenatal care providers have the most potential to increase influenza vaccination rates. Further studies are needed to understand the barriers of health care providers regarding influenza vaccination in Ecuador.